2014
DOI: 10.1002/cyto.a.22452
|View full text |Cite
|
Sign up to set email alerts
|

In search of antiaging modalities: Evaluation of mTOR‐ and ROS/DNA damage‐signaling by cytometry

Abstract: This review presents the evidence in support of the IGF-1/mTOR/S6K1 signaling as the primary factor contributing to aging and cellular senescence. Reviewed are also specific interactions between mTOR/S6K1 and ROS-DNA damage signaling pathways. Outlined are critical sites along these pathways, including autophagy, as targets for potential antiaging (gero-suppressive) and/or chemopreventive agents. Presented are applications of flow- and laser scanning- cytometry utilizing phospho-specific Abs, to monitor activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 153 publications
1
37
0
1
Order By: Relevance
“…Metformin has been shown to effectively inhibit ROS production in cells by suppressing oxidative phosphorylation [30, 31]. We examined levels of ROS in the cells and found that the baseline levels differed between them.…”
Section: Resultsmentioning
confidence: 99%
“…Metformin has been shown to effectively inhibit ROS production in cells by suppressing oxidative phosphorylation [30, 31]. We examined levels of ROS in the cells and found that the baseline levels differed between them.…”
Section: Resultsmentioning
confidence: 99%
“…45 Intriguingly, mTORC1 regulates mitochondrial quality and ROS, 63 suggesting that inhibition of mTORC1 and mitochondrial ROS by aPC may be mechanistically linked. Because the regulation of mitochondrial ROS and mTORC1 is mutual, 64 additional studies are required to decipher the exact mechanism through which aPC regulates mTORC1 and mitochondrial ROS.…”
Section: 5152mentioning
confidence: 99%
“…A decrease in autophagy activity leads to accumulation of protein aggregates, which negatively affect cell function and lead to damage and degeneration of mitochondria, thus contributing to aging [28]. …”
Section: Introductionmentioning
confidence: 99%